2022
DOI: 10.1038/s41598-022-14175-0
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Plasmodium vivax malaria on executive and cognitive functions in elderlies in the Brazilian Amazon

Abstract: The exact path leading to cognitive impairment that goes beyond malaria is unclear, but it appears to be the result of interactive factors. Time of exposure to disease and recurrences are potentially major determinant variables. Cognitive impairment is described mainly in children, rarely in adults. The disease in high endemic areas usually does not affect elderlies, because of acquired immunity over time. However, this population is relatively more frequently sick in lower endemic areas, such as in the Amazon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
3
0
3
Order By: Relevance
“…The cognitive deficits of nSM may be persistent, but the evolution of cognitive and behavioral impairment is poorly understood ( 12 , 28 ). Persistent cognitive impairment may affect social, economic and cultural development in malaria-endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive deficits of nSM may be persistent, but the evolution of cognitive and behavioral impairment is poorly understood ( 12 , 28 ). Persistent cognitive impairment may affect social, economic and cultural development in malaria-endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment, assessed by an indicator of intellectual function, Intelligence-IV (WPPSI-IV) which measures parameters such as verbal comprehension and working memory, was reported in children between 2 and 7 years old who had suffered at least one P. vivax malaria episode compared to children who had never had malaria 104 . More recently it was reported that acute P. vivax malaria may be associated with long-term impairment of executive and cognitive functions in the elderly 105 .…”
Section: Plasmodium Infection Can Cause Neurocognitive Impai...mentioning
confidence: 99%
“…Além disso, sequelas cognitivas relacionadas à memória de trabalho, à compreensão verbal, à organização perceptiva e ao raciocínio abstrato também foram observadas em crianças como resultado de um único episódio de MnG nessa localidade (13), bem como no Estado do Pará (14). Recentemente, sequelas cognitivas e das funções executivas foram relatadas oito meses após o episódio de malária vivax não grave em idosos no estado do Amazonas (15).…”
Section: Figura 1 -Alterações Cognitivas Após a Malária Não Grave (A)...unclassified
“…Sobre a dinâmica e a persistência das sequelas da MnG; apesar de alguns estudos registrarem efeitos com duração de em torno de nove meses após o último episódio malárico (10,13,15), um estudo na Tailândia não detectou efeito negativo no desempenho escolar em crianças e adolescentes com histórico de malária há mais de dois anos (16). Isso contrasta com a situação observada em casos de malária grave.…”
Section: Figura 1 -Alterações Cognitivas Após a Malária Não Grave (A)...unclassified
See 1 more Smart Citation